Protective astrogenesis from the SVZ niche after injury is controlled by notch modulator THBS4. - Benner, Eric J.; Dominic, Luciano; Jo, Rebecca; Abdi, Khadar; Páez-González, Patricia; Sheng, Huaxin; Warner, David S.; Liu, Chunlei; Eroglu, Cagla; Kuo, Chay T. (Springer Nature, 2013)
Postnatal/adult neural stem cells (NSCs) within the rodent subventricular/subependymal zone (SVZ/SEZ) generate Doublecortin (DCX)+ neuroblasts that migrate and integrate into olfactory bulb circuitry1,2 . Continuous production of neuroblasts is controlled by SVZ microenvironmental niche3,4 . It is generally believed that enhancing neurogenic activities of endogenous NSCs may provide needed therapeutic options for disease states and after brain injury. However, SVZ NSCs can also differentiate into astrocytes. It remains unclear if there are conditions that favor astrogenesis over neurogenesis in the SVZ niche, and if astrocytes produced there exhibit different properties from others in the brain. We have uncovered that SVZ-generated astrocytes express high levels of Thrombospondin-4 (Thbs4)5,6 , a secreted homopentameric glycoprotein, in contrast to cortical astrocytes which are Thbs4low. We found that localized photothrombotic/ischemic cortical injury initiates a marked increase in Thbs4hi astrocyte production from the postnatal SVZ niche. Tamoxifen-inducible nestin-CreERtm4 lineage-tracing demonstrated that it is these SVZ generated Thbs4hi astrocytes, and not DCX+ neuroblasts, that home-in on the injured cortex.

This robust post-injury astrogenic response required SVZ Notch activation, modulated by Thbs4 via direct Notch1 receptor binding and endocytosis to activate downstream signals, including increased Nfia transcription factor expression important for glia production7 . Consequently, Thbs4KO/KO animals showed severe defects in cortical injury-induced SVZ astrogenesis, instead producing cells expressing DCX from SVZ to the injury sites. These alterations in cellular responses resulted in abnormal glial scar formation after injury, and significantly increased microvascular hemorrhage into the brain parenchyma of Thbs4KO/KO animals. Taken together, these findings have significant implications for post-injury applications of endogenous and transplanted NSCs in the therapeutic setting, as well as disease states where Thbs family members play important roles.
Post-injury protective astrogenesis from SVZ niche is controlled by Notch modulator Thbs4
https://openpolicyfinder.jisc.ac.uk/id/publication/4008
Keywords: Células madre neurales; Neurobiología del desarrollo; Astrocitos; SVZ; Neural stem cells; Neurogenesis; Astrocyte